The Impact of Teamwork Management of Accounting Personnel on the Accounts Receivable Management Efficiency of Small and Medium Enterprises in Bangkok - Piromsod, Amornrat; Kijrungrojjarean, Preyanuch (Journal of Humanities and Social Sciences, Rajapruk University, 2024)
This research aims to study 1) the level of teamwork management of accounting personnel of small and medium enterprises in Bangkok 2) the level of accounts receivable management efficiency of accounting personnel of small and medium enterprises in Bangkok 3) the effects of teamwork management on accounts receivable management efficiency of small and medium enterprises in Bangkok. Sample in this research was 400 accounting personnel of small and medium enterprises in Bangkok using stratified random samplling. Data were collected via questionnaire with an IOC validity level of 0.67 – 1.00 and reliability of 0.70 – 0.83 and analyzed by frequency, percentage, mean, and standard deviation and analyzed the effects by multiple regression. The results showed that 1) the teamwork management level of accounting personnel of small and medium enterprises in Bangkok was good ( =, SD=0.). Creativity was the best aspect, among others, followed by coordination, cooperation, continuous improvement, and communication respectively 2) accounts receivable management efficiency of small and medium enterprises (SMEs) in Bangkok was high ( =, SD=0.). The aspect of work quality was the highest, among others, followed by cost, time, and quantity, respectively. 3) Teamwork management in all aspects, except commutation, affected the efficiency of accounts receivable management of small and medium enterprises in Bangkok at a significant level of .05